2023
DOI: 10.1002/aenm.202204095
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated Ionic Electroresponse of Asymmetric Bio‐Hydrogels with Unremitting Power Output

Abstract: Cytomembranes with efficient ionic selectivity and energy circulation, essential for biological activities in multicellular organisms, are a source of inspiration for man‐made biomedical devices. However, current man‐made soft systems mainly imitate simple and passive cytomembranes behaviors, restrained by the grand challenge that lies at the meeting point of synchronous engineering of both (dynamic) ionic selectivity and (passive) transcellular‐like potential in one structure. Here a dynamically differentiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…78,79 Most natural hydrogels exhibit a certain degree of ionization in water, rendering them electrically responsive. Notable natural hydrogels employed in electrically driven applications include chitosan, 72,80 silk fibroin, 81,82 gelatin, 83,84 cellulose, 85,86 alginate, 87,88 agarose, 89 and dual network hydrogels formed from these materials in combination with each other or synthetic polymers. 90 For instance, Sun et al fabricated chitosan/ PEG fibers through a wet spinning process from a mixed chitosan and PEG solution, investigating the influence of factors such as fiber diameter, crosslink density, electric field strength, pH, and ionic concentration on the electrically driven properties of the fibers 91,92 Kim et al reported a chitosan/ P(HEMA) hydrogel system featuring an interpenetrating polymer network structure, demonstrating rapid deformation capabilities with a bending angle of 351 achieved in 18 seconds at a voltage of 10 V. 70 Purely natural polymer-based hydrogels exhibit superior biocompatibility and degradability compared to synthetic counterparts.…”
Section: Molecular Design Of Electrically Driven Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…78,79 Most natural hydrogels exhibit a certain degree of ionization in water, rendering them electrically responsive. Notable natural hydrogels employed in electrically driven applications include chitosan, 72,80 silk fibroin, 81,82 gelatin, 83,84 cellulose, 85,86 alginate, 87,88 agarose, 89 and dual network hydrogels formed from these materials in combination with each other or synthetic polymers. 90 For instance, Sun et al fabricated chitosan/ PEG fibers through a wet spinning process from a mixed chitosan and PEG solution, investigating the influence of factors such as fiber diameter, crosslink density, electric field strength, pH, and ionic concentration on the electrically driven properties of the fibers 91,92 Kim et al reported a chitosan/ P(HEMA) hydrogel system featuring an interpenetrating polymer network structure, demonstrating rapid deformation capabilities with a bending angle of 351 achieved in 18 seconds at a voltage of 10 V. 70 Purely natural polymer-based hydrogels exhibit superior biocompatibility and degradability compared to synthetic counterparts.…”
Section: Molecular Design Of Electrically Driven Hydrogelsmentioning
confidence: 99%
“…Fig.4Main molecular structure of E-hydrogel actuators including homopolymers, copolymers and naturally derived polymers 65,[69][70][71][72][73]. …”
mentioning
confidence: 99%
“…Moreover, the measured J-V curves also exhibit rectification behavior, which weakens with ion migration and water evaporation. [28][29][30] As the current response slowly decreases after reaching its peak due to water evaporation and saturation of ionic gradients, the rectification also weakens; therefore, we recorded the J-V and current-time curves of the WDHEG under a squarewave bias voltage (from +2 to −2 V) after operating for different times (Figure 3e,f). As shown in Figure 3e, ion rectification can be observed in the formed diode-like heterojunction, where the current at a positive voltage (+2 V) is considerably larger than that at a negative voltage (−2 V).…”
Section: Working Mechanismmentioning
confidence: 99%
“…[28] Recently, an anion-cation heterostructured hydrogel with a current rectification ratio reaching 4.5 has been designed for moisture electricity generation; the hydrogel can adjust the ion gradients through ion rectification to achieve a long-term, uninterrupted output, with a voltage of 0.1 V and current of 0.4 μA. [29,30] Several HEGs based on the streaming potential and simultaneous use of asymmetric structures (e.g., heterojunctions) have been reported; however, their mechanism remains unclear. [18,24,30,31] Herein, we report a high-performance WDHEG induced by capillary infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional commercial sorbents, such as silica gels and zeolites, commonly exhibit a low water collection capacity and require high energy consumption for water release. Tremendous efforts have been conducted to develop high-performance water harvest materials such as inorganic salts, metal–organic frameworks (MOFs), aerogels, natural wood, and hydrogel composites hygroscopic salts. , Although such materials provide constructive concepts for moisture capture, their poor cyclic durability and low water-releasing performance still hinder their broad applications, such as desiccants for dehumidification. Two key points should be considered for designing a high-performance atmospheric moisture harvester: (1) desiccants should provide strong attraction to moisture with favorable exposed active area to the air to water molecules capture continuously; (2) on the contrary, the interaction between water and desiccants should be weakened when releasing the captured moisture. , Therefore, the ideal water harvesters should exhibit both highly hygroscopic properties and facilitate concurrently efficient water transportation from the surface to the internal space concurrently.…”
Section: Introductionmentioning
confidence: 99%